Times Higher Education World University Rankings for 2012—2013 and Prospects of Science Development in Armenia - Haroutiunian, T. (Наука та інновації, 2014)
The article covers Times Higher Education World Universities Rankings and the criteria, according to which these universities are chosen. Most of them are in North America and Europe and represent Anglo-Saxon school, In the list of top universities appears more and more technical and natural science Asian universities as a result of increasing the number of research universities. The possibility of establishing a research university in Armenia, as well as circumstances that can promote or impede it are considered. The megaprojects implemented in Armenia are presented and the role of research universities in the promotion and establishment of these projects is substantiated.